PIEZORESISTIVE SENSOR BASED ON ECOFLEXÂ® WITH MULTIWALLED CARBON NANOTUBE AND CARBON BLACK - Fathan Fikri Makarim, Muhammad
Piezoresistive sensors have garnered significant attention in both the industrial and medical fields in recent years. These sensors measure changes in resistance caused by applied force. Piezoresistive sensors must possess good sensitivity, durability, and reliability under various environmental conditions. A non-conductive polymer as the sensor substrate matrix requires the addition of conductive fillers to reduce resistance, allowing for accurate resistance change readings. In this study, a piezoresistive sensor was successfully fabricated using Ecoflex® based on Multiwalled Carbon Nanotube (MWCNT) and Carbon Black (CB). The sensor fabrication was assisted by Isopropyl Alcohol (IPA) as a solvent to disperse conductive materials in Ecoflex®. This study explored the effects of sensor dimensions, shape, and temperature. Tensile tests and Scanning Electron Microscopy (SEM) were also conducted to determine the material strength and evaluate the distribution of conductive fillers in the sensor. Furthermore, the sensor thickness was varied between 0.5 to 2 mm, and the width between 3 and 5 mm. The results showed that the sensor could produce high linearity and low hysteresis at a thickness of 2 mm and a width of 5 mm. A composition of 1 wt% MWCNT and 7 wt% CB was chosen as the minimum carbon composition with sufficiently low resistance, measured at 8.66 k?. Next, variations in the sensor's shape were made, with both normal and sandwich structures. The results indicated that the sandwich-structured sensor exhibited a linearity and sensitivity of 0.9881 and 3.75, respectively. The sensor demonstrated good durability and reliability after undergoing electromechanical testing for 1500 cycles. The addition of conductive materials to Ecoflex® resulted in a 75% reduction in material strength. This sensor also showed resistance changes when subjected to temperature increases.